Moral Legitimacy and Joint Purpose: A Literature Review on the Ethical Foundations of Collaborative Organizations - Grace Yulianti; Dadang Irawan (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2026)
This qualitative literature review explores the ethical foundations of collaborative organizations by examining the interplay between moral legitimacy and joint purpose. Drawing from recent scholarship in organizational ethics, stakeholder theory, and virtue ethics, the review highlights how organizations achieve moral legitimacy through shared values, inclusive governance, and ethically anchored missions. Joint purpose emerges as a unifying force that fosters trust, identity, and stakeholder commitment across complex collaborations. The synthesis reveals that organizations sustaining both moral legitimacy and joint purpose are more adaptive, ethically resilient, and capable of creating long-term value. The review also identifies theoretical gaps and suggests directions for future research on moral agency and collective value creation within hybrid organizational forms